APBNag Pada Tiga Nagari Di Kabupaten Tanah Datar : Faktor Komitmen, SDM, Dan Laporan Keuangan - Sri Adella Fitri; Tedi Amria (AKUNTANSI 45, 2023)
This study aims to examine the influence of Commitment, Readiness of Human Resources, and Financial Reporting on the preparation of State Budgets conducted in three villages in the Tanah Datar area. The research was conducted in three nagari in the Tanah Datar area, namely: Sungai Tarab Nagari, Padang Laweh Nagari, and Pasie Laweh Nagari. Research conducted using mixed-methods research methods, and in taking samples using purposive sampling technique. Where the population of the study comes from the head of the nagari guardian and the nagari employees (apparatus), secretaries, treasurers. Sampling of data in this study using questionnaires and interviews. The data samples processed were 30 questionnaires and 3 interviewees. As well as the samples used from internal (primary) and secondary (external) data. Meanwhile, to analyze the sample using a stepwise or multiple linear analysis technique. The results of the study show that commitment, human resources and financial reports have a significant influence on the preparation of the APBNag. This really shows that commitment, human resources, and financial management for the preparation of the State Budget for the Three Nagari in the Tanah Datar District Area.